Peran Anuitas, Nilai Sekarang Bersih (NPV), dan Internal Rate of Return (IRR) dalam Evaluasi Investasi - Nurfadila, Alif Fa'is; Corry, Julyana Fahreeta; Solehah, Aim Matus Noer; Kurniasari, Diva; Pandin, Maria Yovita R. (Jurnal Manajemen Bisnis dan Keuangan, 2025)
Investment evaluation is a crucial component in the strategic decision-making process of companies, particularly amid fluctuating and uncertain economic conditions. This study aims to analyze the role of the Annuity, Net Present Value (NPV), and Internal Rate of Return (IRR) methods in assessing investment feasibility among companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. The research employs a quantitative approach with a descriptive-analytical method. The sample consists of 13 public companies selected through purposive sampling. Data were collected from annual financial reports and processed using SPSS version 27. The results indicate that companies in the banking and telecommunications sectors exhibit relatively stable cash flows and generate consistent Annuity values. Several firms, such as PT Indosat, PT Astra, and PT Bank Mandiri, recorded high positive NPV and IRR values, reflecting strong investment feasibility. In contrast, PT Gudang Garam and PT Semen Indonesia showed negative NPV and IRR values, suggesting potential investment loss risks. However, regression and correlation statistical tests revealed no significant relationship among the Annuity, NPV, and IRR methods. These findings indicate that each method provides a distinct perspective in evaluating investment performance and does not directly influence one another. Although the relationships among the three methods are not statistically significant, their simultaneous application remains essential, as they complement each other. This multidimensional approach is crucial for offering a more comprehensive understanding and supporting more accurate, rational, and strategic investment decisions amid market uncertainty.